Uporaba sistema RTK GNSS v slalomu za merjenje časa od vratc do vratc - Supej, Matej (Šport (Ljubljana), 2022)
Photocell times are most commonly measured in alpine skiing for performance analysis. Although photocell times are measured with high accuracy, the method also has some limitations in performing detailed time analysis, which is very welcome in alpine skiing. Therefore, the aim of the present study was to demonstrate a method for calculating time from trajectories measured with a high-resolution global navigation satellite system (RTK GNSS). Eight skiers were measured under simulated slalom competition conditions, and we compared the times obtained from the RTK GNSS system with the photocell times. The results showed no statistically significant time discrepancies between the photocells and the times calculated by RTK GNSS. The gate-to-gate times obtained with the RTK GNSS system allowed for a detailed performance analysis. Thus, the study demonstrated the usefulness of such a timing system as well as its advantages over conventional photocell timing. Calculating times from the high-resolution RTK GNSS trajectories has proven to be a robust tool for accurate performance analysis in slalom.
Keywords: alpsko smučanje; biomehanika; navigacijski sistemi; slalom; šport; uspešnost